DESCRIPTIVE ANALYSIS OF ADOLESCENT KNOWLEDGE ABOUT STUNTING - Reny Eka Saputri; Mutiarawati Mutiarawati (Universitas Karya Husada Semarang, 2025)
Handling stunting cases is still a major focus in Indonesia. Stunting as a public health problem related to chronic malnutrition in children has become an important issue in Indonesia, especially among adolescent age groups who can contribute to the prevention of stunting in the future. This study aims to determine the description of adolescent knowledge about stunting. This study uses a quantitative descriptive approach with a survey through a questionnaire. The population of all class X students at MAN Kota Tegal was 467 people. Determination of the sample using the Slovin formula, the number of research samples was 215 people. Inclusion criteria: Class X students, aged between 15-16 years and willing to be a research respondent. Data were analyzed univariately. The results showed that most of the respondents were in the moderate category as many as 100 people (46.5%). In the category of good knowledge level as many as 82 people (38.1%) and the category of poor knowledge level as many as 33 people (15.3%). The level of knowledge of adolescents related to stunting still needs to be improved. Most respondents already understand the general knowledge of stunting, but lack understanding related to the long-term impact of stunting, how to prevent stunting in adolescence and specific nutritional handling of stunting in the family.